Robert Ludlum's The Bourne objective [large type] - Lustbader, Eric (Lustbader, Eric. New Jason Bourne novel., 2010)
The Central Intelligence training program Treadstone produced two graduates of equal skill and determination --Jason Bourne and a vicious Russian mercenary, Leonid Arkadin. As Bourne's destiny circles closer to Arkadin's, it becomes clear that the eventual collision of these men is not of their own making. Someone else has been watching and manipulating them. Someone who wants to know, "Who is the more deadly agent?"